Correlation of Platelet Distribution Width (PDW) and Troponin I in Acute Myocardial Infarction - -, Maulinda Putri; Refli Hasan; Rahmad Isnanta (TALENTA Publisher, Universitas Sumatera Utara, 2020)
Background. Coronary artery disease (CAD) is caused by narrowing of the coronary arteries. In the event of acute myocardial infarction (AMI), there will be an increase in heart markers. Several studies have examined the relationship between Platelet Distribution Width (PDW) and AMI, but there is no specific correlation with troponin as the most sensitive and specific cardiac biomarker for AMI. This study aims to see the correlation PDW values with troponin I in patients with AMI. Method. This study was a cross-sectional method to determine the correlation of PDW variable values ​​with troponin I in patients with AMI. In this study, the sample consisted of 64 people. Results. There is a moderate correlation between PDW and troponin I (r2= 0.72, p <0.001). There is a strong correlation with positive direction between PDW and Troponin I in patients with AMI based on the onset of chest pain (<6 hours and > 6 hours : r2 = 0.647 p <0.001and r2 = 0.756, p <0.001). Conclusion. Platelet Distribution Width (PDW) is strongly correlated with Troponin I in patients with AMI, and based on chest pain onset also has a significantly positive correlation.